Serum and Urine Albumin and Response to Loop Diuretics in Heart Failure - Charokopos, Antonios (Clin J Am Soc Nephrol, 2019)
BACKGROUND AND OBJECTIVES: Diuretic resistance can limit successful decongestion of patients with heart failure. Because loop diuretics tightly bind albumin, low serum albumin and high urine albumin can theoretically limit diuretic delivery to the site of action. However, it is unknown if this represents a clinically relevant mechanism of diuretic resistance in human heart failure. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: In total, 208 outpatients with heart failure at the Yale Transitional Care Center undergoing diuretic treatment were studied. Blood and urine chemistries were collected at baseline and 1.5 hours postdiuretic administration. Urine diuretic levels were normalized to urine creatinine and adjusted for diuretic dose administered, and diuretic efficiency was calculated as sodium output per doubling of the loop diuretic dose. Findings were validated in an inpatient heart failure cohort (n=60). RESULTS: Serum albumin levels in the outpatient cohort ranged from 2.4 to 4.9 g/dl, with a median of 3.7 g/dl (interquartile range, 3.5–4.1). Serum albumin had no association with urinary diuretic delivery (r=−0.05; P=0.52), but higher levels weakly correlated with better diuretic efficiency (r=0.17; P=0.02). However, serum albumin inversely correlated with systemic inflammation as assessed by plasma IL-6 (r=−0.35; P<0.001), and controlling for IL-6 eliminated the diuretic efficiency-serum albumin association (r=0.12; P=0.12). In the inpatient cohort, there was no association between serum albumin and urinary diuretic excretion (r=0.15; P=0.32) or diuretic efficiency (r=−0.16; P=0.25). In the outpatient cohort, 39% of patients had microalbuminuria, and 18% had macroalbuminuria. There was no correlation between albuminuria and diuretic efficiency after adjusting for kidney function (r=−0.02; P=0.89). Results were similar in the inpatient cohort. CONCLUSIONS: Serum albumin levels were not associated with urinary diuretic excretion, and urinary albumin levels were not associated with diuretic efficiency.